Cr3+-doped broadband near infrared diopside phosphor for NIR pc-LED. (May 2022) - Fang, Limin; Hao, Zhendong; Zhang, Liangliang; Wu, Hao; Wu, Huajun; Pan, Guohui; Zhang, Jiahua
Highlights: Emission band broadening from 132 nm to 197 nm with still high emission efficiency in CaMgSi2O6 :Cr 3+ phosphor are realized by increasing Cr 3+ doping concentration. CaMgSi2 O6 :Cr 3+ phosphor demonstrates high thermal stability to meet applications. The as fabricated NIR pc-LEDs can offer photoelectric efficiency of 18.12% for the output NIR with the bandwidth of 150 nm, or 11.60% for the bandwidth of 187 nm. Abstract: Broadband Near-infrared phosphors have attracted great attention for its potential applications in pc-LED as a novel light source for substance measurements based on NIR spectroscopy. Here, CaMgSi2 O6 : x Cr 3+ diopside phosphor were prepared by high temperature solid-state reaction. The Cr 3+ emission band undergoes a red-shift from 772 nm to 822 nm followed with band broadening from 132 nm to 197 nm with the increase of x from 0.25% to 6%. Highly thermal stability with the quenching temperature as high as 355 °C for 1% and 236 °C for 4% Cr 3+ concentrations are observed. NIR pc-LEDs were fabricated and high NIR output power of 42.04 mW for the bandwidth of 150 nm and 23.73 mW for a more broaden bandwidth of 187 nm are achieved at 100 mA drive current, respectively. Our results suggest that CaMgSi2 O6 :Cr 3+ phosphors have great potential for applications in broadband NIR pc-LED applications. Graphical abstract: SYNOPSIS . To develop efficient NIR phosphors with the emission band as broad as possible is the key segment for broadband NIR pc-LED light sources. Image, graphical abstract